Sleep Disorders in Late-Life Depression - Katharina Merry Apriliani; dr. Soetjipto (Faculty of Medicine, Universitas Airlangga, 2020)
Depression is an important mental health problem in developed societies, and as many as 50%-90% of patients with depression complain of sleep disorders. In the elderly, sleep disorders comorbid depressive disorders are getting worse. Late-life Depression (LLD) is often not detected because the symptoms are less specific than younger age. It even provides an independent risk factor impact on suicide ideas and behaviour. Causative risk factors of sleep disorders in Late-life Depression are biological and non-biological factors that form the basic of pharmacological and non- pharmacological management.